Simultaneous recording of shadowgrams and schlieren images for the study of plasma assisted aerodynamics - Machado, Jose Marcio [UNESP]; Yang Shiyou,; Abe, Nancy Mieko; Passaro, Angelo (IOS Press, 2010)
This work describes an optical device for the simultaneous recording of shadowgrams and schlieren images, and some results are presented concerning its applications to the study of plasma assisted flow control in airfoil models. This approach offers many advantages in comparison to other methods, specially because the use of tracer particles (like smoke in wind tunnels) is not required for the experiments, thus avoiding contaminations in the electric discharges or air flows. Besides, while schlieren images reveal the refractive index gradients in the area of study, shadowgrams detect the second order spatial derivatives of the refractive indexes. Therefore, the simultaneous recording of these different images may give interesting information about the phenomena under study. In this paper, these images were used to confirm the existence of vortex structures in the flow induced by corona discharges on airfoil models. These structures are a possible explanation for the effects of drag reduction and lift force increasing, which have been reported in experiments of plasma assisted Aerodynamics.
Keywords: Plasma assisted aerodynamics; corona discharges; air flow control